PRELIMINARY SURVEY OF THE PATHOLOGICAL MARCH IN THE DISEASE OF PARKINSON AND THE AQUATIC REHABILITATION THROUGH I SWIM HIM CRAWL. (Fiep Bulletin - online, 2014)
To minimizes motivates loss of march in individuals with Parkinson's disease in the group is the literary abyss. Individuals with Parkinson's disease plows attacked severely in the march. Being known that the Parkinson's disease is compromising of the central nervous system, for the loss of cells of the black substance and dopamine, causing sensation of fatigue, less readable calligraphy, speaks monotonous, depression, lapses of memory, muscular pains, part paresis, and manifestations practice medicine as tremor, rigidity, iciness, bradicinesis, and symptoms no motors as: depression, insomnia, cognitive disturbances, of the speech, breathing, urinary, dizziness and that the dopamine plays important part, being neurotransmitter of the ganglions of the base influencing the operation of this circuit and facilitating the direct road and inhibiting the indirect road, we have as objective verifies the use of aquatic exercises as strategy of march improvement in individuals with Parkinson's disease. Used 02 individuals, male, with age among 35/40 years with treatment in Cemeaes (Macaé-RJ-Brazil), for 12 months. That is a degenerative cerebral disease, characterized by progressive loss of the memory and of other cognitive functions, that you/they harm the patient in their activities of daily life and in his/her social and occupational acting. Previous literatures elapse on individuals (Cruz, 2006) that used aquatic exercises, that you/they computed the following results: with duration exercises of + 30 minutes, making 20 breathings to each series of exercises, they happened an intense muscular fatigue, committing the natural movements, how to elevate arms or walk, and the patients didn't get to finish the exercises. With exercises of 3 series of 20 repetitions with dumbbells for the hands, there was not alteration in those patterns. With the present study it is aimed at to study the influences of the swimming as strategy for the improvement of the march in individuals attacked by the Parkinson's disease, with age between 35 and 45 years.
Keywords: Parkinson; swimming; march